BAKTERI PADA TUBUH IKAN GURAMI (Osphronemus gouramy) AKIBAT INFESTASI EKTOPARASIT Argulus sp. (Bacterial Isolate in Gourami (Osphronemus gouramy) as the Result of the Infestation of Ectoparasites Argulus sp.) - M. Irfan Maulana T. Syihab; Dwi Suryanto; Zulham Apandy Harahap; Orbita Roiyan Dhuha (AQUACOASTMARINE, 2015)
Argulus sp. are parasites that act as mediators for viruses or bacteria frequentlycausing diseases by leaving a bite scar. This study was aimed to know potential pathogenicbacterial in the internal and external organs of gourami as result of ectoparasites Argulus sp.infestation. Twelve Argulus sp. were infested on gourami for 14 days. The isolation of thebacterial of the gourami and water was conducted using dilution methods. Bacterialcharacteristic was conducted to their morphology and biochemical properties followed byidentification of the bacterial. Two bacterial species were found in the samples of fish andwater, i.e. Corynebacterium aquaticum and Micrococcus luteus.Keywords : Osphronemus gouramy, Argulus sp., Corynebacterium aquaticum,Micrococcus luteus.